"Playing it like a professional": Approaches to ensemble direction in tertiary institutions. (May 2013) - Harrison, Scott; O'Bryan, Jessica; Lebler, Don
This article reports on a case study of three directors of large ensembles within a large conservatoire and the ways in which they attempted to scaffold their students into professional music careers. The core aim in this article is to respond to the question "What is the role and function of the ensemble experience on the training of the professional musician?" The study reported on here formed part of a larger project into ensemble assessment practices. However as the study progressed, it became clear that each director perceived that their responsibilities to their students extended well beyond the institutional imperatives of reporting on progress and assessment practices. The sub-questions that relate to this aspect of the study therefore included: "What is the rationale for activities within the ensemble?" "How does the ensemble director facilitate and enable this learning experience?" and "What activities does the director see as intrinsic to the overall ensemble experience?" Using a case study approach, the ensembles involved were observed and their directors were interviewed. Artifacts were also used to support the data generated. These included course outlines, detailed rehearsal expectations and other university prerequisites. The data are presented as narrative accounts of each director. While Directors centered their practices on short-term rehearsal and performance outcomes, they were also keenly aware of the need for students to develop generic musicianship skills and to ensure the development of self-management strategies for life after the conservatoire.